Hypothyroidism and Ramadan fasting - Mousa-Al-Reza Hadjzadeh; Roghayeh Pakdel; Parichehr Hayatdavoudi; Mohsen Nematy (Journal of Fasting and Health, 2014)
Introduction: Fasting during the holy month of Ramadan is an obligation for all adult, healthy Muslims. As several studies have indicated, both fasting and energy restriction can alter thyroid hormone metabolism and affect the clinical features and well-being of hypothyroid patients. Hypothyroidism is more prevalent among women and the elderly. Its prevalence has been reported to be 4-8% of the general population. Despite the large body of animal research on fasting, few human studies have focused on Ramadan fasting and its impacts on hypothyroid patients. Materials & Methods: PubMed and Google scholar databases were searched using keywords such as Ramadan, fasting, hypothyroidism, and food restriction. Animal and human studies, which were highly relevant to the topic, were selected. Results: Four animal and 7 human studies were included in this article. We found that levothyroxine dosage should be increased for hypothyroid patients from the beginning of the month until 15-20 days after the end of Ramadan. Discussion: Fasting can change the concentration of thyroid hormones, thyroid-stimulating hormone level, and the associated metabolisms both in animals and humans. As the results indicated, hypothyroid individuals, who fast during the month of Ramadan, particularly women and the elderly, may suffer from thyroid hormone changes. For these patients, levothyroxine dosage should be increased to 25-50 µg/per day from the beginning of Ramadan until 15-20 days after the end of this month. Conclusion: An increased dose of levothyroxine during Ramadan is recommended for hypothyroid patients, particularly women and the elderly.